2016
DOI: 10.1016/j.plasmid.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A large conjugative Acinetobacter baumannii plasmid carrying the sul2 sulphonamide and strAB streptomycin resistance genes

Abstract: whole genome sequence data was used to determine the plasmid content of strain A297 32 (RUH875), the reference strain for the globally disseminated multiply resistant A. baumannii 33 clone, global clone 1(GC1). A297 contains three plasmids. Two known plasmids were 34 present; one, pA297-1 (pRAY*), carries the aadB gentamicin, kanamycin and tobramycin 35 resistance gene and another is an 8.7 kb cryptic plasmid often found in GC1 isolates. The 36 third plasmid, pA297-3, is 200 kb and carries the sul2 sulphonamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 29 publications
0
64
1
Order By: Relevance
“…Otherwise, our experimental studies revealed that AbaR GI is maintained over time in A144 as well as in A155 without antimicrobial pressure for at least one month. We can assume that there is a balance between conservation and plasticity of particular regions of the accessory genome, as previously described for the core genome regions of A. baumannii (Touchon et al, 2014;Hamidian et al, 2016). The other remaining "sedentary" modules, the cas genes from the type IF-b CRISPR-Cas system, RGP1, and RGP4, did not show signs of microevolution.…”
Section: Discussionmentioning
confidence: 84%
“…Otherwise, our experimental studies revealed that AbaR GI is maintained over time in A144 as well as in A155 without antimicrobial pressure for at least one month. We can assume that there is a balance between conservation and plasticity of particular regions of the accessory genome, as previously described for the core genome regions of A. baumannii (Touchon et al, 2014;Hamidian et al, 2016). The other remaining "sedentary" modules, the cas genes from the type IF-b CRISPR-Cas system, RGP1, and RGP4, did not show signs of microevolution.…”
Section: Discussionmentioning
confidence: 84%
“…Antibiotic resistance genes were detected with the curated version of the ARG-ANNOT database available at the SRST2 site (Gupta et al, 2014;Inouye et al, 2014), rpoB SNP mutations were assessed comparing the sequences against described resistance mutations (Giannouli et al, 2012;PĂ©rez-Varela et al, 2017), and virulence factors with VFDB (Chen et al, 2016), using the read-based search program ARIBA (Hunt et al, 2017). Plasmid replicons were detected with a custom database composed of 30 genes involved in plasmid replication, stabilization and mobilization from Acinetobacter plasmids (Bertini et al, 2010;Salto et al, 2018); some additional plasmids (Gao et al, 2011;Hamidian et al, 2012Hamidian et al, , 2016Zhang et al, 2013;Jones et al, 2014;Blackwell and Hall, 2017;Hamidian et al, 2017) were also included (full database Supplementary Dataset S1); and analyses were undertaken using ARIBA software v2.12.1 (Hunt et al, 2017). To account for potential variation in surface proteins or other virulence factors, a custom-made collection of A. baumannii virulence factors ( Supplementary Table S6) was searched against our isolates using phmmer (Eddy, 2011;Eijkelkamp et al, 2011Eijkelkamp et al, , 2014Harding et al, 2013;Scott et al, 2014;Weber et al, 2015;Lee et al, 2017).…”
Section: Antibiotic Resistance and Traits Associated With Infectionmentioning
confidence: 99%
“…One of the key features of the A. baumannii genome is an open pan genome with a wide variety of mobile genetic elements, particularly integrons and transposons in genomic islands, some of which are known as resistance islands due to the presence of multiple antibiotic resistance genes ( Fournier et al, 2006 ; Bonnin et al, 2012 ; RamĂ­rez et al, 2013 ). Resistance genes are also plasmid-borne and in A. baumannii , plasmids range from as small as 2 kb to more than 100 kb in size ( Gallagher et al, 2015 ; Hamidian et al, 2016a , b ). The large plasmids of A. baumannii are often the focus of analyses due mainly to the presence of multiple antibiotic resistance genes and the self-transmissible nature of these plasmids ( Hamidian et al, 2014a , b , 2016a ; Hamidian and Hall, 2014 ) although small plasmids have been highlighted especially those that harbor antibiotic resistance genes ( D’Andrea et al, 2009 ; Merino et al, 2010 ; Grosso et al, 2012 ; Hamidian et al, 2012 , 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance genes are also plasmid-borne and in A. baumannii , plasmids range from as small as 2 kb to more than 100 kb in size ( Gallagher et al, 2015 ; Hamidian et al, 2016a , b ). The large plasmids of A. baumannii are often the focus of analyses due mainly to the presence of multiple antibiotic resistance genes and the self-transmissible nature of these plasmids ( Hamidian et al, 2014a , b , 2016a ; Hamidian and Hall, 2014 ) although small plasmids have been highlighted especially those that harbor antibiotic resistance genes ( D’Andrea et al, 2009 ; Merino et al, 2010 ; Grosso et al, 2012 ; Hamidian et al, 2012 , 2016b ). Despite the importance of plasmids in the potential transmission of resistance and virulence genes in A. baumannii , there has been surprisingly very little experimental work done on the basic biology of these plasmids.…”
Section: Introductionmentioning
confidence: 99%